Nano material containing cerium element, spray and application of nano material to improvement of quality of wheat grains

Nanomaterials containing cerium are synthesized through chemical precipitation methods and used for wheat spraying. This solves the problem in the existing technology that improving wheat quality requires a long time and a large amount of resources, and achieves efficient and economical improvement of wheat quality.

CN119344331APending Publication Date: 2025-01-24XINJIANG ACADEMY OF AGRI & RECLAMATION SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411486195.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing methods to improve wheat quality mainly rely on plant genetic breeding technology, which requires years of time and a large amount of germplasm resources, resulting in high costs and low resource utilization.

Method used

A cerium-containing nanomaterial is synthesized through chemical precipitation method, and cerium nitrate and polyacrylic acid are used as raw materials to prepare a nano-spraying agent and spray it on wheat plants to improve the nutritional quality of wheat.

Benefits of technology

The nanomaterial can effectively improve the quality of wheat seeds, including increasing the content of crude protein, wet gluten content, and precipitation index, reducing fatty acid values, simple synthesis methods, common equipment, and suitable for industrial large quantities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119344331A_ABST
    Figure CN119344331A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of agricultural production, and particularly relates to a cerium-containing nanometer material, a spray and application of the cerium-containing nanometer material and the spray in improving the quality of wheat grains. According to the invention, cerium nitrate and polyacrylic acid are reacted through a chemical precipitation synthesis method to synthesize a cerium-containing nano material (PNC). The result of the embodiment shows that the PNC prepared by the invention can be used as a spraying agent to be mixed with a surfactant and then sprayed on the middle upper part of wheat, the crude protein content, wet gluten and precipitation index of wheat grains after spraying are obviously higher than those of common wheat grains, and the fatty acid value is obviously reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of agricultural production, and specifically relates to a nano material containing cerium element, a spray and application of the nano material in improving the quality of wheat grains. Background Art

[0002] With the improvement of people's living standards, the demand for high-quality special wheat is growing all over the country. Wheat is an important food crop with a large planting area in Xinjiang. Studies have shown that wheat quality is controlled by genetic factors, cultivation measures and environmental factors. As a primary agricultural product, the reduction in wheat quality will undoubtedly reduce the economic benefits of growing wheat. Most of the existing methods to improve wheat quality are plant genetic breeding technology, which requires many years and a large amount of germplasm resources. This undoubtedly increases the cost of achievement transformation, promotion and production.

[0003] Plant nanobiology is an emerging interdisciplinary subject with unique ideas for improving wheat quality. Most of the existing methods for improving wheat quality are plant genetic breeding techniques, which require many years of time and a large amount of germplasm resources. Therefore, the use of nanomaterials that can improve wheat quality is of great significance for improving economic benefits and resource utilization. Summary of the invention

[0004] The purpose of the present invention is to provide a nanomaterial containing cerium. The method provided by the present invention can not only effectively improve the nutritional quality of wheat, but also has a simple synthesis method and common equipment, which is suitable for industrial mass preparation. The synthesized nanomaterial can be used after filtering.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The invention provides a nano material containing cerium element. The nano material is synthesized from cerium nitrate and polyacrylic acid through a chemical precipitation synthesis method.

[0007] Preferably, the extinction coefficient of the nanomaterial is 3 cm -1 M -1 .

[0008] The present invention also provides a nano spraying agent, which comprises the above-mentioned nano material.

[0009] Preferably, the spraying concentration of the spraying agent is 100-200 mg / L.

[0010] Preferably, the spray further contains 0.05% by volume of a surfactant.

[0011] The present invention also provides a method for preparing a nano spray agent, which specifically comprises the following steps:

[0012] S1. Take cerium nitrate and polyacrylic acid and fully dissolve them in double distilled water respectively, mix the dissolved solutions, and vortex mix to obtain a mixed solution;

[0013] S2, adding the mixed solution in step S1 into ammonia water and stirring to obtain a light yellow viscous solution;

[0014] S3, centrifuging the light yellow viscous solution in step S2, and obtaining the nano spray agent by centrifuging and purifying the supernatant after centrifugation.

[0015] Preferably, in step S1, cerium nitrate and polyacrylic acid are weighed in a mass fraction ratio of 6:25 and dissolved in water to obtain 0.432 g / mL cerium nitrate solution and 0.9 g / mL polyacrylic acid solution, respectively. Preferably, the vortex condition in step S1 is 2500 rmin -1 Vortex at 400 rpm for 15 min.

[0016] Preferably, in step S2, the mixed solution is added dropwise into 2 times the volume of 30% ammonia water at 500 rmin. -1 Stir for 24 h.

[0017] The present invention also provides application of the nano material or nano spraying agent in improving the quality of wheat grains.

[0018] Beneficial effects of the present invention:

[0019] The invention uses cerium nitrate and polyacrylic acid as raw materials and synthesizes a nano spraying agent through a chemical precipitation method. The nano spraying agent can be used after simple purification.

[0020] The materials used in the present invention are cerium nitrate and polyacrylic acid, both of which are widely used and moderately priced industrial raw materials with moderate preparation costs.

[0021] The synthesis method of the invention is simple, the equipment used is common, and it is suitable for industrial mass preparation.

[0022] The synthesized nanomaterial of the present invention can be used after filtering, and can still maintain catalytic activity in high temperature, acidic, or saline-alkali environments.

[0023] The nano material obtained by the method of the present invention can effectively improve the quality of wheat grains. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0025] Figure 1 The appearance of wheat grains after being treated with different solutions for 33 days;

[0026] Figure 2 This is an analysis chart of the average crude protein content of wheat grains after being treated with different solutions for 33 days;

[0027] Figure 3 This is an analysis chart of the average wet gluten content of wheat grains after being treated with different solutions for 33 days;

[0028] Figure 4 This is an analysis chart of the average precipitation index of wheat grains after being treated with different solutions for 33 days;

[0029] Figure 5 This is an analysis chart of the average falling index of wheat grains after being treated with different solutions for 33 days;

[0030] Figure 6 This is an analysis chart of the average fatty acid value of wheat grains after being treated with different solutions for 33 days;

[0031] Figure 7 This is an analysis chart of the average capacity of wheat grains after being treated with different solutions for 33 days. DETAILED DESCRIPTION

[0032] The present invention provides a nano material (PNC) containing cerium element. The nano material is synthesized by chemical precipitation synthesis method from cerium nitrate and polyacrylic acid. The absorbance value of the finally obtained PNC is scanned at 220nm-700nm on an ultraviolet spectrophotometer, and double distilled water is used to establish a baseline and zero adjustment. The final concentration of PNC is calculated by substituting the absorbance value at 271nm into the Lambert-Beer formula, and the extinction coefficient of PNC is determined to be 3cm -1 M -1 .

[0033] The preparation method of the cerium-containing nanomaterial (PNC) of the present invention specifically comprises the following steps:

[0034] S1. Take cerium nitrate and polyacrylic acid and fully dissolve them in double distilled water respectively, mix the dissolved solutions, and vortex mix to obtain a mixed solution;

[0035] S2, adding the mixed solution in step S1 into ammonia water and stirring to obtain a light yellow viscous solution;

[0036] S3, centrifuging the light yellow viscous solution in step S2, and obtaining the nano spray agent by centrifuging and purifying the supernatant after centrifugation.

[0037] In the above step S1, cerium nitrate and polyacrylic acid are weighed in a mass fraction ratio of 6:25 and dissolved in water to obtain 0.432 g / mL cerium nitrate solution and 0.9 g / mL polyacrylic acid solution, respectively. The vortex condition in step S1 is 2500 rmin -1 The mixed solution in step S2 was added dropwise to 2 times the volume of 30% ammonia water and vortexed at 500 rmin for 15 min. -1 Stir for 24 h.

[0038] The invention uses a mixture of a nano material (PNC) containing cerium and a surfactant (Silwet L-77) to spray on wheat plants; and a pure water control group is set to mix with the surfactant and spray on the wheat plants. The spray concentration of the spray is 100-200 mg / L, and the spray also contains 0.05% by volume of the surfactant.

[0039] At the wheat maturity stage (33 days after treatment), the wheat was threshed and impurities were removed, and the differences in crude protein content, wet gluten content, sedimentation index, landing index, fatty acid value and capacity between the experimental group and the control group were detected and analyzed.

[0040] The wheat variety used in the present invention is the main variety grown in southern Xinjiang: Xindong 55, and the seeds of this variety were purchased from Tahe Seed Industry in Aral City, Xinjiang.

[0041] In order to further illustrate the present invention, the technical solution provided by the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0042] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art.

[0043] Example 1 Preparation of PNC

[0044] Accurately weigh 1.08g of cerium nitrate in a 10ml centrifuge tube, and add 2.5mL of double distilled water to dissolve it. Accurately weigh 4.5g of poly(acrylic acid) [PAA] in a 50mL centrifuge tube, and add 5mL of double distilled water to fully disperse it until there are no large lumps.

[0045] Mix the two solutions and vortex at 2500 rpm. -1 Vortex at 400 rpm for 15 min.

[0046] Subtract 0.5 cm from the tip of the 1 mL blue pipette tip, and use a 1 mL dragon pipette to add the mixed solution drop by drop into a 50 mL beaker containing 15 mL of 30% ammonia water while stirring. -1 The mixture was stirred for 24 h to obtain a light yellow viscous solution.

[0047] The obtained solution was divided into 1.5 mL centrifuge tubes, centrifuged at 3900 g for 1 h at room temperature, and the supernatant was aspirated. The supernatant was transferred to a 15 mL 10 kDa ultrafiltration tube, 1 mL of double distilled water was added, and the supernatant was centrifuged at 4500 rmin. -1 Centrifuge for 45 minutes and discard the liquid in the outer tube to remove unreacted small molecules. The steps using the ultrafiltration tube should be repeated at least 6 times.

[0048] The purified PNC was scanned on a UV spectrophotometer at 220 nm-700 nm for absorbance, and double distilled water was used to establish the baseline and zero. The final concentration of PNC was calculated by substituting the absorbance value at 271 nm into the Lambert-Beer formula, where the extinction coefficient of PNC is 3 cm -1 M -1 PNCs were stored in a refrigerator at 4°C.

[0049] Example 2 Wheat sowing and spraying

[0050] Select wheat seeds with full grains, uniform size and no damage. Set up a test plot with a row length of 3 meters, a row spacing of 20 cm, and a total plot area of ​​3m 2 On October 2, 2023, the seeds were sown in the experimental plot, 2 cm per seed, and watered for 20 minutes after sowing. 3 / mu.

[0051] The wheat was treated on May 14, when it was in the early stage of grain filling. A 100 mg / L nanomaterial mixed solution containing 0.05% Silwet L-77 was evenly sprayed on the middle and upper parts of the wheat in the entire plot using a 5L spraying pot. The wheat was sprayed with pure water containing 0.05% Silwet L-77 as a control group.

[0052] Comparative analysis of Example 3 spraying agent after use

[0053] At the wheat maturity stage, i.e. 33 days after treatment, the treated wheat and the control wheat were harvested, threshed and impurities were removed. The appearance of wheat grains after 33 days of treatment with different solutions was photographed as follows: Figure 1 shown.

[0054] Figure 1The control group is the control group that applied clean water containing surfactant, and PMO is the treatment group that applied nanomaterials + surfactant. It can be seen from the figure that the grains of the treatment group are fuller in appearance than those of the control group, and the color of some grains is darker than that of the control group, that is, the keratinization is relatively better than that of the control group.

[0055] 3.1 Analysis of crude protein content in wheat grains

[0056] The crude protein content of wheat grains in the experimental group and the control group after 33 days of treatment was measured using a near-infrared analyzer (SupNIR-1230) produced by Beijing Jitian Instruments. Each group was measured three times and the average value was taken. Figure 2 shown.

[0057] The results of crude protein content determination showed that the average crude protein content of wheat grains treated with the spraying agent was significantly higher than that of the control group.

[0058] 3.2 Analysis of wet gluten content in wheat grains

[0059] The wet gluten content of wheat grains in the experimental group and the control group after 33 days of treatment was determined using a near infrared analyzer (SupNIR-1230) produced by Beijing Jitian Instruments. Each group was measured 3 times and the average value was taken. The results are shown in Figure 3 shown.

[0060] The results of wet gluten content determination showed that the average wet gluten content of wheat grains treated with the spraying agent was significantly higher than that of the control group.

[0061] 3.3 Analysis of Sedimentation Index of Wheat Grains

[0062] The wheat sedimentation index is highly correlated with quality indicators such as protein content and wet gluten content, and is one of the important individual indicators reflecting the quality of wheat. A higher sedimentation index indicates high gluten content and good quality, which is conducive to making high-quality bread and other baked products. A lower sedimentation index may mean low gluten content or poor quality, which may affect the texture and taste of pasta.

[0063] The precipitation index of wheat grains in the experimental group and the control group after 33 days of treatment was measured using a near infrared analyzer (SupNIR-1230) produced by Beijing Jitian Instruments. Each group was measured 3 times and the average value was taken. The results are shown in Figure 4 The results of sedimentation index test showed that the average sedimentation index of wheat grains treated with the spraying agent was significantly higher than that of the control group.

[0064] 3.4 Falling number analysis of wheat grains

[0065] Wheat falling index is an important indicator for measuring wheat quality, which reflects the activity of α-amylase in wheat grains. Wheat falling index, also known as falling number, is measured by the total time from the viscometer entering the water heater to the viscometer stirring and falling into the gelatinized suspension, and this time is expressed in seconds. The falling number directly reflects the activity of α-amylase in wheat grains: if the α-amylase activity is low, the falling number is high; conversely, if the α-amylase activity is high, the falling number is low.

[0066] The near infrared analyzer (SupNIR-1230) produced by Beijing Jitian Instruments measured the falling number of wheat grains in the experimental group and the control group after 33 days of treatment. Each group was measured 3 times and the average value was taken. The results are as follows: Figure 5 The results of the falling index test showed that the average falling index of wheat grains treated with the spray agent was not much different from that of the control group.

[0067] 3.5 Analysis of fatty acid values ​​of wheat grains

[0068] The fatty acid value of wheat grains is also an important quality indicator that determines the grade and quality of flour. The higher the grade of flour, the lower its fatty acid value.

[0069] The fatty acid values ​​of wheat grains in the experimental group and the control group after 33 days of treatment were measured using a near infrared analyzer (SupNIR-1230) produced by Beijing Jitian Instruments. Each group was measured 3 times and the average value was taken. The results are shown in the figure. Figure 6 The results of fatty acid value determination showed that the average fatty acid value of wheat grains treated with the spraying agent was lower than that of the control group.

[0070] 3.6 Analysis of bulk density of wheat grains

[0071] The capacity of wheat grains is one of the important indicators to measure wheat quality. For the same wheat variety, the higher the capacity, the fuller the grain and the higher the flour yield.

[0072] The bulk density of wheat grains in the experimental group and the control group after 33 days of treatment was measured using a near infrared analyzer (SupNIR-1230) produced by Beijing Jitian Instruments. Each group was measured 3 times and the average value was taken. Figure 7 The results of capacity determination showed that the average capacity of wheat grains after spraying was not much different from that of the control group.

[0073] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A nanomaterial containing cerium, characterized in that: The nano material is synthesized from cerium nitrate and polyacrylic acid through a chemical precipitation synthesis method.

2. The nanomaterial according to claim 1, characterized in that: The extinction coefficient of the nanomaterial is 3 cm -1 M -1 .

3. A nano spray agent, characterized in that: The nano spraying agent comprises the nano material according to claim 1.

4. The nano spray agent according to claim 3, characterized in that: The spraying concentration of the spraying agent is 100-200 mg / L.

5. The nano spray agent according to claim 3, characterized in that: The spray also contained 0.05% by volume of a surfactant.

6. A method for preparing a nano spray agent, characterized in that: The following steps are involved: S1. Dissolve cerium nitrate and polyacrylic acid in double distilled water, respectively, mix the dissolved solutions, and vortex mix to obtain a mixed solution; S2, adding the mixed solution in step S1 into ammonia water and stirring to obtain a light yellow viscous solution; S3, centrifuging the light yellow viscous solution in step S2, and filtering and purifying the supernatant after centrifugation to obtain a nano spray agent.

7. The preparation method according to claim 6, characterized in that: In the step S1, cerium nitrate and polyacrylic acid are weighed in a mass fraction ratio of 6:25 and dissolved in water to obtain 0.432 g / mL cerium nitrate solution and 0.9 g / mL polyacrylic acid solution, respectively.

8. The preparation method according to claim 6, characterized in that: The vortex condition in step S1 is 2500 rmin -1 Vortex at 400 rpm for 15 min.

9. The preparation method according to claim 6, characterized in that: In step S2, the mixed solution is added dropwise into 2 times the volume of 30% ammonia water and stirred at 500 rmin. -1 Stir for 24 h.

10. Use of the nanomaterial according to claim 1 or the nano spraying agent according to claim 3 in improving the quality of wheat grains.